Bio-Oil Production From Lignocellulosic Biomass Using Fast Pyrolysis in A Fluidized-Bed Reactor - Duku, Moses Hensley (2015)
Thesis Submitted to the Department of Wood Science and Technology, Kwame Nkrumah University Ofscience and Technology in Partial Fulfilment of the Requirements for the Degree of DOCTOR OF PHILOSOPHY